2017
DOI: 10.1111/jnc.13980
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of TREK‐1 potassium channel exacerbates secondary injury following spinal cord injury in mice

Abstract: Spinal cord injury (SCI) involves complex pathological process which can be complicated by secondary injury. TREK-1 is a member of the two-pore domain potassium (K2P) channel family, which can be modulated by a number of physiological and pathological stimuli. Recent studies suggest that TREK-1 plays an active role in depression, pain and neuroprotection. However, its role in the pathological process after SCI remains unclear. In this study, we tested the expression and function of TREK-1 in spinal cord of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Finally, different ion channels are expressed in OPCs and oligodendrocytes including voltage-gated sodium channels (Tong et al, 2009), voltate-gated calcium channels (Verkhratsky et al, 1990) and diverse potassium channels (Buttigieg et al, 2011;Wang et al, 2011;Hawkins and Butt, 2013;Moroni et al, 2015;Battefeld et al, 2016;Livesey et al, 2016;Fang et al, 2017;Brasko et al, 2017;Larson et al, 2018) which participate in glial cell proliferation, regeneration, oligodendroglia/neuronal and axonal interactions, and Ferrer Progress in Neurobiology xxx (2018) xxx-xxx which modulate oligodendroglial responses to ischemia, excitotoxicity and seizures, among other pathological settings.…”
Section: Expression Of Neurotransmitter Hormone Receptors and Ion Chmentioning
confidence: 99%
“…Finally, different ion channels are expressed in OPCs and oligodendrocytes including voltage-gated sodium channels (Tong et al, 2009), voltate-gated calcium channels (Verkhratsky et al, 1990) and diverse potassium channels (Buttigieg et al, 2011;Wang et al, 2011;Hawkins and Butt, 2013;Moroni et al, 2015;Battefeld et al, 2016;Livesey et al, 2016;Fang et al, 2017;Brasko et al, 2017;Larson et al, 2018) which participate in glial cell proliferation, regeneration, oligodendroglia/neuronal and axonal interactions, and Ferrer Progress in Neurobiology xxx (2018) xxx-xxx which modulate oligodendroglial responses to ischemia, excitotoxicity and seizures, among other pathological settings.…”
Section: Expression Of Neurotransmitter Hormone Receptors and Ion Chmentioning
confidence: 99%
“…TREK-1 channel, which is a novel subtype of two-pore-domain potassium channels, can be activated by mechanical stretch and polyunsaturated fatty acids. Numerous studies have reported that TREK-1 (mainly expressed in brain and spinal cord) channel plays a neuroprotective effect in the process of cerebral ischemic injury ( 14 , 15 ). Treatment with TREK-1 channel agonists can effectively reduce brain damage in animal models of cerebral ischemia and epilepsy, while brain damage cannot be reduced in TREK-1 knockout rats ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…TREK-1 deficient mice showed an exacerbated focal inflammatory response after spinal cord injury (SCI). Furthermore, TREK-1 deficiency enhanced astrogliosis, neuronal apoptosis, demyelination and retarded motor recovery (Fang et al, 2017). Nevertheless, in other reported studies, in the DRG, the microRNA miR-183 expression was decreased and TREK-1 expression was increased in neuropathic pain induced by chronic constriction of sciatic nerve (CCI) (Table 3; Han et al, 2016; Shi et al, 2018).…”
Section: Trek-1 Channelmentioning
confidence: 99%